2012
DOI: 10.1371/journal.pone.0041693
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-149 Inhibits Proliferation and Cell Cycle Progression through the Targeting of ZBTB2 in Human Gastric Cancer

Abstract: An increasing body of evidence indicates that miR-149 can both suppress and promote tumor growth depending on the tumor type. However, the role of miR-149 in the progression of gastric cancer (GC) remains unknown. Here we report that miR-149 is a tumor suppressor in human gastric cancer. miR-149 expression is decreased in GC cell lines and clinical specimens in comparison to normal gastric epithelial cell and tissues, respectively. The expression levels of miR-149 also correlate with the differentiation degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
106
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 42 publications
7
106
0
1
Order By: Relevance
“…miRNA is thereby a potential diagnostic and prognostic marker of TSCC with therapeutic potential (18)(19)(20). Previous studies revealed that miR-149 was downregulated in colorectal cancer, breast cancer, gastric cancer, glioma, melanoma and non-small cell lung cancer (21)(22)(23)(24)(25)(26). This study investigated the expression, biological functions and molecular mechanisms of miR-149 in TSCC.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…miRNA is thereby a potential diagnostic and prognostic marker of TSCC with therapeutic potential (18)(19)(20). Previous studies revealed that miR-149 was downregulated in colorectal cancer, breast cancer, gastric cancer, glioma, melanoma and non-small cell lung cancer (21)(22)(23)(24)(25)(26). This study investigated the expression, biological functions and molecular mechanisms of miR-149 in TSCC.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, miR-149 was reported to decrease glioma cell growth and invasion through targeting protein kinase B signaling (24). Furthermore, Wang et al (23) found that miR-149 suppressed cell proliferation and cell cycle progression via the blockade of zinc finger and BTB domain containing 2 in human gastric cancer. At present, little is known with respect to the role of miR-149 in TSCC.…”
Section: Discussionmentioning
confidence: 99%
“…31 Ectopic expression of miR-149-5p in gastric cancer cells inhibits proliferation and cell cycle progression. 29 Furthermore, the expression of miR-149-5p was previously demonstrated to have inverse correlation with the invasive capability and epithelial-to-mesenchymal transition of the NSCLC cells. The ectopic transfection of miR-149-5p increases E-cadherin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, miR-149-5p promotes cell proliferation. 27 Recent study revealed that miR-149-5p expression is significantly downregulated and plays an important role as a tumor suppressor 28 in some cancers, such as gastric cancer, 29 astrocytomas, 30 glioma, 31 colon, and rectum carcinoma (colorectal cancer (CRC)). 32 Overexpression of miR-149-5p was found to inhibit the viability and invasion of cells in vitro and have prognostic and therapeutic implications on CRC.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-149C>T polymorphisms have been widely investigated in various cancers, such as gastric cancer, lung cancer, colorectal cancer, nasopharyngeal carcinoma, and breast cancer (Luo et al, 2012;Wang et al, 2012;Øster et al, 2013;Wilting et al, 2013;Zhang et al, 2013). Two studies reported that miRNA-149C>T polymorphisms are associated with the development of HCC (Liu et al, 2010;Kim et al, 2012).…”
Section: Discussionmentioning
confidence: 99%